The role of entrepreneurship in reducing poverty in agricultural communities - Dzingirai, Mufaro (Emerald, 2022)
Purpose Entrepreneurship has increasingly become a subject of interest for scholars and policymakers in an attempt to reduce poverty in agricultural communities across the world, especially in Africa. Accordingly, the purpose of this paper is to examine the role of entrepreneurship in reducing poverty in agricultural communities of Lower Gweru, Zimbabwe.